Experiences of TVET college leaders in managing workplace job-related gossip in one municipality, Gauteng Province - Xaba, Siphamandla Johan (University of the Free State, 2024)
The study aimed to investigate the experiences of technical and vocational education and training (TVET) college leaders managing workplace job-related gossip in in one municipality, Gauteng province. The study was informed by the leader-member-exchange theory developed by Dansereau in 1975 and the Evolution of Gossip Theory by the anthropologist Robin Dunbar in 1996. In developing a critical and interpretive understanding of the experiences of TVET college leaders handling workplace job-related gossip, data were created through semi-structured interviews with campus managers, focus group discussions with the head of the department, and document analysis using a qualitative technique. The study found that gossip, a private discourse, can be harmful and duplicitous, reflecting the speaker's true sentiments. It can be positive and negative, affecting and targeting the individual's private life. The study further revealed that managers condemn gossip, while others provide counselling or encourage employees to be mature to foster a culture of love and care, acting reasonably in handling discussions. This approach helps mitigate gossip's negative impact and promotes a healthier work environment. The findings also revealed that managers face substantial obstacles in handling workplace gossip, such as becoming subjects of gossip themselves, often cited incorrectly, employees may perceive themselves as being targeted and misinterpret the managers' motives. Such challenges add complexity to handling gossip-related issues, impeding the effective resolution of these problems. The study, therefore, concludes that the nature of gossip is complex, involving secrecy and potential harm. The study recommends continuous professional development programs that include training enhancing work-related gossip management skills, for managers to better manage interpersonal relationships, encourage open communication, and promote a just culture, which can also help reduce the frequency and consequences of workplace gossip.
Dissertation (M.Ed.(Education Management and Leadership))--University of the Free State, 2024
Keywords: Workplace gossip; TVET college; Managers; Leaders; Employees; HoDs